Home confinement with electronic monitoring.: Offenders’ perspectives in Argentina. (Delito y Sociedad, 2023)
The use of home confinement with electronic monitoring (HCEM) has spread worldwide, and the Republic of Argentina is no exception. However, despite the investigations produced in the Global North, there is no research on how convicted individuals perceive the punitiveness of this type of sanction in our country, and there are very few studies conducted in the rest of the Spanish speaking countries. This study aims to begin to fill that gap by conducting an exploratory study on the perceptions of users of the criminal justice system in the City of Buenos Aires. The results show that the preference of HCEM to prison is equal to or more pronounced than in the Anglo-Saxon context and Europe. The "preferred alternative framework" comparison to imprisonment and the deplorable prison conditions may be influencing this. The role of significant others and children cannot be overlooked either. Contrary to previous studies, the female gender seems to negatively moderate the "tightness" of this alternative penalty. Recognizing the limitations of the sample’s size, this initial exploration allows for future research directions in the Argentinian context or in the rest of the world, and informs criminal and legislative policy.
Keywords: home detention; electronic monitoring; punitiveness; offenders' perspectives; Argentina